(untitled) (Журнал "У". Экономика. Управление. Финансы., 2018)
In the article features of accounting of expenses of auxiliary production are revealed. The relevance of the chosen subject is caused by the fact that auxiliary productions serve the main production, providing it with water, the electric power, transport, etc. Besides, the article considers the reflection order in accounting of operations of auxiliary production and also allocation of costs between the main and auxiliary production is considered.